2022
DOI: 10.1007/s00266-022-02782-1
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Complications for Different Approaches in Gynecomastia Correction: A Systematic Review of the Literature

Abstract: Background Gynecomastia is nowadays a very common disease, affecting a large cohort of patients with different ages. The aim of this literature review is to assess the incidence of complications with all proposed techniques and for combined procedures versus single approach procedures in gynecomastia correction. Materials and Methods A systematic review of the literature was performed to identify all reported techniques for gynecomastia correction covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 125 publications
0
4
1
Order By: Relevance
“…Only a small percentage of our patients developed hematoma, and surgical intervention was required in only one case. The occurrence of seroma or surgical site infection was absent in our patients, which differs from the findings of other authors [ 26 ]. The absence of seroma complications in our study may be attributed to the removal of drains after 3–4 days, suggesting that the use of drains may reduce seroma rates.…”
Section: Discussioncontrasting
confidence: 99%
“…Only a small percentage of our patients developed hematoma, and surgical intervention was required in only one case. The occurrence of seroma or surgical site infection was absent in our patients, which differs from the findings of other authors [ 26 ]. The absence of seroma complications in our study may be attributed to the removal of drains after 3–4 days, suggesting that the use of drains may reduce seroma rates.…”
Section: Discussioncontrasting
confidence: 99%
“…There were no instances of nipple necrosis, seroma, or hematoma. In the literature, the most common reported complications following gynecomastia surgery are hematoma (4.4%–5.8%) and seroma (2.1%–3.9%), 6 together constituting the most common nonaesthetic reason to require a second surgery. 4 , 7 …”
Section: Discussionmentioning
confidence: 99%
“…There were no instances of nipple necrosis, seroma, or hematoma. In the literature, the most common reported complications following gynecomastia surgery are hematoma (4.4%-5.8%) and seroma (2.1%-3.9%), 6 together constituting the most common nonaesthetic reason to require a second surgery. 4,7 In a systematic review, Innocenti et al have already demonstrated that techniques involving liposuction (whether alone or combined with open resection) have lower hematoma rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GYN can be caused by systemic diseases, obesity, endocrine disorders (such as liver cirrhosis, which impairs estrogen inactivation), malignant tumors, and medications, and also idiopathic cause of GYN one of the causes. After treating the underlying disease, GYN commonly lasts for more than 12 months ( 3 ).…”
Section: Introductionmentioning
confidence: 99%